Cu-Ag/SBA-15 nano catalysts for the control of microorganisms in water - Saidulu Ganji; Ramesh Kola; Kumaraswamy Gullapelli; Ramesh Martha (Discover Nano)
Abstract Because of their uniform and regular channels, adjustable pore size, large surface area, controllable wall composition, high hydrothermal stability, ease of functional modification, and good accessibility of larger reactant molecules, mesoporous siliceous SBA-15 is of excellent catalyst carrier that is highly versatile and has been used extensively to prepare a variety of supported catalysts with ideal catalytic properties. In this study, we report the synthesis, characterization, and catalytic application of Cu-Ag/ SBA-15 nanoalloy catalysts towards the control of microorganisms in drinking water has been reported. The Cu-Ag/SBA-15 nanoalloy catalysts with different molar mass ratio of copper to silver (Cu:Ag = 1: 0, 0.75: 0.25, 0.5: 0.5, 0.25: 0.75, 0: 1) keeping 1weight % total loading of copper and silver metals on SBA-15 support have been prepared by incipient wetness impregnation method and characterized by various characterization techniques like, low angle XRD, wide angle XRD, N2-physcisorption and scanning electron microscopy techniques. The anti-bacterial activity of the catalysts was measured qualitatively by testing the presence of coliforms in water after contacting with the catalyst at room temperature. These nanoalloy catalysts found to be effective in controlling the microorganisms in drinking water. Among the series of the catalysts prepared, 0.25Cu-0.75Ag /SBA-15 catalyst showed superior catalytic activity. The high catalytic performance of the catalyst is due to its high surface area.